Teaching English vocabulary to adult learners - Sattarova Saodat Narzullayevna; Ibodullayeva Durdona Golib qizi (Zien Journals, 2021)
Teaching vocabulary is a vital part of any English language course. Many teachers are concerned about how to teach vocabulary. New words have to be introduced in such a way as to capture the students’ attention and place the words in their memories.
Keywords: Pronunciation; Dictionary; Communication; Academic ability